A LoRa-based Remote Gesture Monitoring System Using Deep Learning. Issue 2 (February 2021) - Xie, Junwei; Song, Wei; Gozho, Amanda; Yu, Fan
Abstract: To solve the problems of high power consumption, low transmission distance and low recognition accuracy of the gesture monitoring system of traditional wearable devices, this paper designs a remote gesture monitoring system based on LoRa. In terms of data transmission, LoRa Internet of Things technology is used, which has the characteristics of low power consumption, high speed and long-distance transmission, and can meet the needs of multi-user long-term use. The identification module is built on the remote server and can be used directly without configuration. Based on the multi-sensor data, this paper also designs a deep learning model to complete the task of human gesture recognition, which can recognize 7 kinds of gesture data and the effect meets the expectations.